40 Begriffe für eine Schreibwissenschaft. Konzeptuelle Perspektiven auf Praxis und Praktiken des Schreibens

(Neo-)Kantian Foundation of Foundations: The Göttingen Case - Peckhaus, Volker (New Perspectives on Neo-Kantianism and the Sciences)

Die Neuformierung der Mathematischen Logik im Nachkriegsdeutschland - Peckhaus, Volker (Geschichte der Tagungen am MFO, 1944 bis 1960er Jahre)

Fraenkel, Abraham A. - Peckhaus, Volker (Neue Deutsche Biographie Deutschland Online)

Kritische Mathematik und die Axiomatik Hilberts - Peckhaus, Volker (Der Geist der kritischen Schule. Kantisches Denken in der Tradition von Jakob Friedrich Fries und Leonard Nelson im 20. Jahrhundert: Wirkungen und Aktualität)

Leibniz’s Influence on 19th Century Logic - Peckhaus, Volker (The Stanford Encyclopedia of Philosophy, first published Sep 4, 2009, substantive revision Feb 2, 2024)

Automatische Transkriptionssoftware – ein Erfahrungsbericht. - Schmidt, Rebecca (SozMethode)

Herausforderungen in der inklusiven Mädchenarbeit: Begleitforschung der „Inklusiven anonymen Zuflucht“ des Mädchenhaus Bielefeld e.V. - Richter, Susanne (Inklusiver Kinderschutz – Anforderungen, Herausforderungen, Perspektiven)

Social Impact Bond assetization struggles: A comparative case study of the United Kingdom and Germany - Knoll, Lisa; Fraser, Alec (Economy and Society)

Effects of task difficulty on visual processing speed - Banh, Ngoc Chi; Scharlau, Ingrid

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

Measuring Visual Attention Capacity Across xReality - Biermeier, Kai; Scharlau, Ingrid; Yigitbas, Enes (Proceedings of the 17th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2024))

A mixed‐methods study of the quality of parental support during adolescents' information‐related Internet use as a co‐construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)
Abstract Introduction In Europe, most Internet searches for school‐related tasks are situated at home, where parents can support adolescents. Although the frequency (quantity) of parental support has already been analyzed, a research gap exists concerning the quality of parental support in adolescents' information‐related Internet use. The quality of parental support in the field of homework involvement is known to be a predictor of adolescents' learning motivation and academic achievement, often discussed with regard to self‐determination theory (SDT) in terms of autonomy support, structure, emotional support, and control. These categories were adapted in this study to analyze parents' support in adolescents' Internet searching activities. Methods Using a mixed‐methods approach, we combined quantitative questionnaires and qualitative observations to analyze joint information‐related Internet uses. Therefore, 243 parent–adolescent dyads were surveyed and six parent–adolescent dyads were observed by videography in 2019/2020 in Germany. The adolescents were 11 years old, on average. Results The parents rated all qualities higher than the adolescents. Emotional support was rated highest by both groups, whereas structure was rated lowest. Adolescents' and parents' view on parental support differ. The qualitative study revealed parents' often interfering behavior, whereas emotional support was low. Further, the active role of adolescents was highlighted in both quantitative and qualitative data. Conclusions By combining quantitative and qualitative approaches, we demonstrated a fruitful application of SDT in analyzing the quality of parental support during adolescents' Internet searches at home and shed light on the co‐construction of joint Internet searches.
Keywords: Psychiatry and Mental health; Developmental and Educational Psychology; Social Psychology; Pediatrics; Perinatology and Child Health

Zermelo - Peckhaus, Volker (Neue Deutsche Biographie, Bd. 28: Wettstein - Zwoch)

Leibniz, Gottfried Wilhelm, General Inquiries on the Analysis of Notions and Truths, edited with an English translation by Massimo Mugnai, Oxford University Press: Oxford 2021 (BSHP New Texts in the History of Philosophy) - Peckhaus, Volker (Mathematical Reviews, MR457231)

Tschirk, Wolfgang. "Vom Universum des Denkens. Eine Geistesgeschichte der Logik". Springer: Berlin 2022, xvii, 117 S. - Peckhaus , Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bootstrapping the Open Science culture: The fellowship approach - Heck, Tamara; Steinhardt, Isabel; Rahal, Rima-Maria; Schubotz, Moritz; Scholl, Dominik; Behrens, Sarah (Research Ideas and Outcomes)
Keywords: Open Science

Outcomes-based contracting and public management reform: Lessons from a decade of experimentation - FitzGerald, Clare; Fraser, Alec; Kimmitt, Jonathan; Knoll, Lisa; Williams, James (International Public Management Journal)
Keywords: Public Administration; Business and International Management

Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Parallele Universen des Wissenschaftsmanagements? Ein Vergleich des Wissenschaftsmanagements an Hochschulen und außeruniversitären Forschungseinrichtungen in Deutschland. - Schneider, Sebastian; Mauermeister, Sylvi; Henke, Justus; Aust, Robert (Hochschulmanagement. Zeitschrift für die Leitung, Entwicklung und Selbstverwaltung von Hochschulen und Wissenschaftseinrichtungen.)
The development of good conditions for research is an essential task of research institutions, which in practice is nowadays mostly performed by science managers. Research in the field of science management in Germany mainly refers to developments at universities, whereas little is known about the situation at so called non-university research organisations. At the same time, there are hardly any statistics on the size of the science management in Germa-ny. In order to take first steps towards exploring these parallel universes, this article presents a comparative mapping of science management at universities and non-university research organisations for Germany by drawing on a special analysis of the German Federal Statistical Office and an online survey.

Citizen Science: Laien-Partizipation an Forschung - Göbel, Claudia; Henke, Justus; Mauermeister, Sylvi; Pasternack, Peer (Wissenschaftskommunikation, neu sortiert.)

Gesellschaftlich-demokratische Teilhabe: trotz hochschulischer oder durch hochschulische Bildung? - de Angelis, Moira; Harles, Dorothea; Mauermeister, Sylvi; Aust, Robert (Das Hochschulwesen)

Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.

Conjunctive and additive group work reduce academic procrastination: insights from a vignette study - Koppenborg, Markus; Klingsieck, Katrin B.; Hüffmeier, Joachim (Current Psychology)
Abstract Group work can increase individual effort, performance, and positive affect, if group members perceive their own contribution as indispensable for the group product. A vignette methodology was applied to investigate whether group work may also reduce procrastination. The vignettes described a typical academic assignment, while varying the task structure (individual work vs. conjunctive group work vs. additive group work) and group member ability (high vs. low). For each vignette, student participants ( N = 443) provided ratings on their perceived indispensability, procrastination of the assignment, and affect. When group member ability was high, procrastination was lower in additive group work as compared to individual work. When group member ability was low, procrastination was lower in conjunctive group work as compared to both individual work and additive group work. As predicted, perceived indispensability mediated the difference in procrastination between conjunctive and additive group work. Moderation analyses further revealed that the effects were more pronounced for high trait procrastinators. Further, both types of group work led to increases in task-related positive affect as compared to individual work. By demonstrating the relevance of group work as a social factor, the results should be useful for the extension of existing programs targeting procrastination, and may inspire measures for preventing procrastination by changes in the study environment.
Keywords: General Psychology

GEProS - Entwicklung und Evaluation einer digitalen Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden - Grotegut, Lea
Um Schüler*innenmerkmale korrekt zu beurteilen benötigen Lehrkräfte diagnostische Kompetenz. Insbesondere die genaue Einschätzung nicht-kognitiver Merkmale von Schüler*innen fällt Lehrkräften eher schwer. Dazu zählen auch mögliche Anzeichen für Lern- und Verhaltensauffälligkeiten. Maßnahmen zur Förderung diagnostischer Kompetenz fokussieren bisher größtenteils die Diagnostik fachspezifischer, situativer Urteilsgegenstände, wie Fehlkonzepte im Mathematikunterricht. Systematisch evaluierte Fördermaßnahmen, die das Erkennen und Beurteilen von Lern- und Verhaltensauffälligkeiten bei Schüler*innen fokussieren, existieren bisher nicht.Aus diesem Anlass wurde die digitale, problemorientierte Simulation GEProS zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden entwickelt und systematisch in drei längsschnittlichen, (quasi-)experimentellen Kontrollgruppenstudien evaluiert. Die Ergebnisse zeigen, dass die GEProS einen Mehrwert für die Förderung diagnostischer Kompetenz insbesondere im Bereich selbstbestimmter Motivation bieten kann. Ein integriertes Quiz mit Feedback kann mittels testing effect darüber hinaus der Erwerb deklarativ-konzeptionellen Wissens als zentrale Disposition diagnostischer Kompetenz in GEProS unterstützen. Die Ergebnisse tragen durch das entwickelte Integrative Modell diagnostischer Kompetenz zur Theoriebildung sowie zur Forschung und Entwicklung im Bereich der Förderung diagnostischer Kompetenz bei, indem eine Maßnahme zur Förderung diagnostischer Kompetenz für einen fächerübergreifenden, zeitlich stabilen Urteilsgegenstand systematisch evaluiert wurde. Durch die Ableitung und Berücksichtigung wesentlicher Merkmale digitaler Simulationen trägt diese Arbeit außerdem zur theoretischen Fundierung digitaler Simulationen bei.

Kompetenzentwicklung in der Lehrkräftebildung: der Mehrwert einer digitalen Simulation - Grotegut, Lea; Klingsieck, Katrin B. (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Förderung diagnostischer Kompetenz in der Lehrer*innenbildung birgt zwei Herausforderungen: Erstens bleibt in großen Lehrveranstaltungen wenig Raum für die notwendige Anwendung theoretischen Wissens, zweitens können Fehlentscheidungen in realen diagnostischen Situationen gravierende negative Folgen für Schüler*innen haben. Eine digitale Simulation kann beiden Herausforderungen begegnen. In diesem Beitrag wurde eine digitale, problemorientierte Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden evaluiert und mit einer textbasierten, problemorientierten und einer lehrendenzentrierten Kontrollgruppe verglichen. Die Ergebnisse zeigen positive Effekte für die digitale Simulation hinsichtlich der selbstbestimmten Motivation, aber einen geringeren Wissenszuwachs im Vergleich zum lehrendenzentrierten Setting. Die Selbstwirksamkeit nahm in allen drei Gruppen zu. Eine digitale Simulation bietet in der untersuchten Form somit einen, wenn auch geringen, Mehrwert für die Lehrkräftebildung im Bereich der Kompetenzentwicklung.
Keywords: General Earth and Planetary Sciences; General Engineering; General Environmental Science

Aufschieben, weil man sich schlecht fühlt, oder sich schlecht fühlen, weil man aufschiebt? – Gruppenspezifische Unterschiede im Verhalten und Erleben von Prokrastination - Bobe, Julia; Klingsieck, Katrin B.

Prokrastination und das schlechte Gewissen - Gruppenunterschiede im Erleben und Auftreten von Prokrastination. - Bobe, Julia; Klingsieck, Katrin B.

The Importance of Distrust in AI - Peters, Tobias Martin; Visser, Roel W. (Communications in Computer and Information Science)

Wissenschaft und Alltagserfahrung: Überlegungen zur Wissenschaftsdidaktik der Psychologie - Scharlau, Ingrid (Wissenschaftsdidaktik II: Einzelne Disziplinen)
Keywords: Unterrichtsfach Psychologie

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

Kant and the Role(s) of Doctrines of Methods (Journal of Transcendental Philosophy)

Your Smartphone Is Watching You - Eine technikkritische Untersuchung der menschlichen Freiheit und Antiquiertheit im Zeitalter der Digitaltechnologie - Mac Award, Daria-Leona

Soziale Eingebundenheit als Schlüssel?! - Perspektiven zur Förderung von student engagament in der Hochschullehre - Steinhardt, Isabel; Thielsch, Angelika (Aktive Teilhabe fördern. ICM und Student Engagement in der Hochschullehre)

A mixed-methods study of the quality of parental support during adolescents' information-related Internet use as a co-construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)

Schreibfokussierte Graduiertenförderung: Reflexive Spezialisierung für interdisziplinäre Forschungskontexte - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre)

What is AI Ethics? Ethics as means of self-regulation and the need for critical reflection - Alpsancar, Suzana (International Conference on Computer Ethics 2023)

Bolzano, Bernard: Briefe an Michael Josef Fesl 1837–1840. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.3) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1512.01036)

Wolfram, Stephen. Dropping in on Gottfried Leibniz. In: Unravelling Complexity: The Life and Work of Gregory Chaitin, hg. v. Francisco Antonio Doria und Shyam Wuppuluri, World Scientific: Hackensack, NJ 2020, 49–81 - Peckhaus, Volker (Mathematical Reviews MR4450759)

Bolzano, Bernard. Briefe an Michael Josef Fesl 1841–1845. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.4). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete ZBl 1512.01037)

Wolfgang Tschirk: Vom Universum des Denkens. Eine Geistesgeschichte der Logik. Springer: Berlin 2022 - Peckhaus, Volker (Mathematische Semesterberichte)

Open Research Practices and Cultural Change: A Commentary on “(Why) Are Open Research Practices the Future for the Study of Language Learning?” - Steinhardt, Isabel; Mauermeister, Sylvi; Schmidt, Rebecca (Language Learning)
Keywords: Open Science; Open Science Practices; Cultural Change

The Bot Delusion. ChatGPT and anticipated consequences for research communication - Wieczorek, Oliver; Steinhardt, Isabel; Schneijderberg, Christian; Schmidt, Rebecca; Mauermeister, Sylvi
The reproduction of social inequalities through artificial intelligence (AI) and machine learning via artificial neural networks (ANN) has been demonstrated empirically in various areas of society, for instance in policing and personnel hiring decisions. Yet, a broader discussion is missing to what extent ANN technological developments may affect the scientific enterprise and reinforce or mitigate existing structural inequalities in academia. Focusing on publications and citations as main currencies in science, the anticipated consequences of ChatGPT on the research communication of existing and new knowledges are discussed in three scenarios, which echo the social structures in academia.

Die Rechtfertigung des Kapitalismus und die Kritik. Der neue Geist des Kapitalismus von Luc Boltanski und Ève Chiapello - Knoll, Lisa (Soziologische Gegenwartsdiagnosen 3)

Ernst Schröder’s Algebra of Logic and the ‘Logic of the Ancient - Peckhaus, Volker (Aristotle’s Syllogism and the Creation of Modern Logic: Between Tradition and Innovation, 1820s–1930s (Bloomsbury Studies in the Aristotelian Tradition))

Nakano, Anderson: On Ramsey’s Reason to Amend Principia Mathematica’s Logicism and Wittgenstein’s Reaction, Synthese 199 (2021), 2629–2646. - Peckhaus, Volker (Mathematical Reviews MR4341825)

Schappacher, Norbert. Framing Global Mathematics. The International Mathematical Union between Theorems and Politics, Springer: Cham 2022 - Peckhaus, Volker (Mathematical Reviews MR4461006)

Aranda, Victor. Completeness: From Husserl to Carnap. Logica Universalis 16 (2022), 57–83 - Peckhaus, Volker (Mathematical Reviews MR4451488)

Floyd, Juliet und Felix Mühlhölzer, Wittgenstein’s Annotations to Hardy’s Course of Pure Mathematics. An Investigation of Wittgenstein’s Non-Extensionalist Understanding of the Real Numbers, Springer: Cham 2020 (Nordic Wittgenstein Studies, 7). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07214204)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 6: Taschennotizbücher1931–32. Anmerkungen, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2022, xiii, 192 S. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07469681)

Hogan, Desmond, “Kant and the Character of Mathematical Inference”, in: Carl Posy et al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 126–154 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1570.01020)

Schlimm, Dirk, "Pasch’s Empiricism as Methodological Structuralism." In: Erich H. Reck und Georg Schiemer (eds.), The Prehistory of Mathematical Structuralism, Oxford: University Press 2020, 88–105 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.01017)

Bellomo, Anna und Guillaume Massas, Bolzano’s Mathematical Infinite. The Review of Symbolic Logic 16, No. 1 (2023), 59–113 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1515.01010)

Tschirk, Wolfgang, Vom Universum des Denkens. Eine Geistesgeschichte der Logik, Springer: Berlin 2022 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.03007)

Herrmann, Kay (Hg.), Grete Henry-Hermann: Philosophie – Mathematik – Quantenmechanik. Texte zur Naturphilosophie und Erkenntnistheorie, mathematisch-physikalische Beiträge sowie ausgewählte Korrespondenz aus den Jahren 1925 bis 1982. Springer VS: Wiesbaden 2019, xv + 664 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1506.01002)

Hannah Arendt and Politics - Robaszkiewicz, Maria Anna; Weinman, Michael D.

Leibniz, Zeitschrift für Didaktik der Philosophie und Ethik

Kants kategorischer Imperativ im sprachsensiblen Philosophieunterricht. Sapere Aude – Habe Mut, dich Primärquellen zu bedienen. (gekürzt) - Albus, Vanessa; Jost, Leif Marvin (Textarbeit im Philosophie- und Ethikunterricht)

Humanismus und Philosophieunterricht - Albus, Vanessa (Humanität als religionspädagogisches und -didaktisches Leitmotiv)

Leibniz. Ein Rationalist im Kanon des Philosophieunterrichts - Albus, Vanessa; Blank, Andreas (ZDPE)

Barbara Schmitz: Was ist ein lebenswertes Leben? Philosophische und biographische Zugänge. Stuttgart Reclam 2022 - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Qualitätsmanagement im Verbundvorhaben Communities of Practice für eine innovative Lehrerbildung NRW (COMeIN). Abschlussbericht - Buhl, Heike M.; Eickelmann, Birgit; Niemann, Jan; Raneck-Kuhlmann, Anna; Drossel, Kerstin

"Immerhin wurden Erfahrungen mit digitalen Tools gemacht" - Mauermeister, Sylvi; Steinhardt, Isabel; Bloch, Roland; Lohner, David; Schulz, Anja (Sozialmagazin)
Der Hoffnung auf einen nachhaltigen Digitalisierungsschub von Studium und Lehre an Hochschulen in Corona-Zeiten folgte vielerorts Ernüchterung. Die fast vollständige und überwiegend begrüßte Rückkehr zur Präsenzlehre führte dazu, dass wenig darüber reflektiert wurde, welche Erfahrungen mit der Online-Lehre gemacht wurden und worauf sich aufbauen lässt. Im Frühjahr 2023 wurde ein Open-Space-Workshop zur Unterstützung der (digitalen) Lehre durchgeführt. Die Ergebnisse zeigen: Den Lehrenden kommt eine zentrale Rolle für die weitere Digitalisierung zu.

Wie hältst du es mit der Wahrheit? Bilder von Wissenschaft und Wissenschaftler*in-Sein angesichts von Diagnosen der Postfaktizität. - Haker, Christoph; Otterspeer, Lukas (Entgrenzungen. Beiträge zum 28. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft)

Gegen eine Militarisierung des Pädagogischen. Über die Folgen des Ukraine-Kriegs für die politische Bildung - Haker, Christoph; Otterspeer, Lukas (Ungewissheit als Erfahrung in der Demokratie)

Wissenschaftsbezogener Rechtspopulismus/-extremismus. Eine Podiumsdiskussion. - Haker, Christoph; Lehnert, Esther; Otterspeer, Lukas; Thole, Werner (Polarisierte Welten. Verhandlungen des 41. Kongresses der Deutschen Gesellschaft für Soziologie in Bielefeld 2022)

Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.
Keywords: General Medicine

Geschlechter - Verhältnisse - Widersprüche. Eine Einleitung - Hoffarth, Britta; Mentzing, Stina; Richter, Susanne (Geschlechter - Verhältnisse - Widersprüche)

Multiple Verhandlungen: ›Cancel Culture‹ aus Perspektive feministischer Digitalisierungsforschung - Richter, Susanne (Geschlechter - Verhältnisse - Widersprüche)

Geschlechter - Verhältnisse - Widersprüche

Cancel Culture als Arena politisierter Wissenskonflikte Am Beispiel einer Debatte um rassistische Begriffe im Sommer 2022 - Richter, Susanne (Verhandlungen des 41. Kongresses der Deutschen Gesellschaft für Soziologie in Bielefeld 2022)

Turning Disciplinary Differences from a Brake into a Motor in Higher Education (Collaboration) - Sloane, Hannah Sabrina; Schmöckel, Sabrina

First steps towards real-time assessment of attentional weights and capacity according to TVA - Banh, Ngoc Chi; Scharlau, Ingrid (Abstracts of the 65th TeaP)

"ProGRess" - Erste Evaluationsergebnisse eines Anti-Prokrastinationstrainings auf Basis des Zürcher Ressourcen Modells (ZRM). - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Reduce procrastination to improve students' health - First analyses of an intervention study. - Schneider, Tamara; Klingsieck, Katrin B.

Framing Goals of Mathematics Support Measures - Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Schürmann, Mirko; Biehler, Rolf; Schaper, Niclas (Practice-Oriented Research in Tertiary Mathematics Education)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,2: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2023, xv, 229–475 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete, Zbl. 1527.01035)

Du Châtelet et la tradition critique de la Bible. De la ‘philofolie’ aux Examens - Hagengruber, Ruth Edith (La Lettre clandestine n° 30: Émilie Du Châtelet et la littérature clandestine. Moreau, P.F. & Seguin, M.S. (Eds.). Paris)

Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die „dritte Wissensdimension“. Eine Epistemologie für eine neue Wissenswelt - Hagengruber, Ruth Edith (Sitzungsberichte der Leibniz-Sozietät der Wissenschaften 150/151, Jahrgang 2022: „Cyberscience – Wissenschaftsforschung und Informatik. Digitale Medien und die Zukunft der Kultur wissenschaftlicher Tätigkeit. Arbeitskreis „Emergente Systeme/Informatik und Gesellschaft“ der Leibniz-Sozietät der Wissenschaften zu Berlin in Kooperation mit der Gesellschaft für Wissenschaftsforschung“)

Transitivitätscharakteristika als Werkzeug in der systematischen qualitativen Metaphernanalyse - Karsten, Andrea; Schwede, Jana; Körber, Miriam; Scharlau, Ingrid (Die Praxis der systematischen Metaphernanalyse)

Kollaborative Autoethnographien digitaler Praktiken. Eine konzeptionelle, methodische und theoretische Einführung zu einem Lehr-Forschungsprojekt im ersten Corona-Semester - Steinhardt, Isabel (DNGPS Working Paper)
Keywords: Open Science; kollaborative Autoethnographie

Hundertstelmillimeter - Scharlau, Ingrid (Reflexive Schreibwissenschaft)

Reflexive Schreibwissenschaft

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne)
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz

Époque Émilienne
Keywords: Émilie Du Châtelet; History of Science; Kant; Newton; Maupertuis; Voltaire

Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die (Un-)Sichtbarkeit von (offenen) Bildungsmaterialien in der Soziologie - Hiebl, Johannes; Steinhardt, Isabel; Bigos, Michael (die hochschule)
Der Beitrag beschäftigt sich mit dem Gebrauch von sogenannten Open Educational Resources (OER) innerhalb der deutschsprachigen Soziologie. OER sind Lehr-und Lernmaterialien, die öffent-lich und frei von Kosten zugänglich sind sowie unter einer offenen Lizenz stehen, die es erlaubt, das Material frei zu nutzen, zu vervielfältigen und zu bearbeiten. Um diese Form der Bereitstellung von Lehr-und Lernmaterial zu fördern, sind im deutschen Sprachraum in den letzten Jahren verschie-dene digitale Infrastrukturen entstanden, die an einzelnen Hochschulstandorten, aber auch hochschulübergreifend Lehrenden zur Verfügung stehen, um dort ihr Material zu veröffentlichen. Es wurden 37 dieser Repositorien untersucht. Darüber hinaus wurde auch die Videoplattform YouTube nach soziologischem Lehr-und Lernmaterial durchforstet. Der Beitrag stellt den Zeitverlauf und die Akteur:innen der OER-Veröffentlichungen dar. Anschließend soll mithilfe eines praxistheoretischen Vokabulars die Lehre innerhalb der Soziologie aufgeschlüsselt und ein möglicher Bezug zu den empirischen Ergebnissen hergestellt werden.
Keywords: Soziologie; Praxistheorie; Repositorien; Open Educational Resources; OER

Dem eigenen Anspruch auf der Spur - Ternes, Doris; Bernhard, Nadine; Gewinner, Irina; Goller, Antje; Lohner, David; König, Karsten; Röwert, Ronny; Steinhardt, Isabel; Thielsch, Angelika (Hochschulen in der Pandemie. Impulse für eine nachhaltige Entwicklung von Studium und Lehre)
Der Beitrag geht der Frage nach, welchen Herausforderungen Lehrende durch die digitale Lehre im ersten Corona-Semester 2020 begegnet sind und welche Strategien sie für deren Bewältigung gewählt haben. Als Datengrundlage dienendazu sechs autoethnographische Stories, entstanden im Projekt AEDiL. Diese haben sich als wertvolles Material erwiesen, um unmittelbare Einblicke in das Lehrhandeln und die -planung zu erhalten und die weiterführende Analyse zu ermöglichen. Dabei offenbarte sich der gemeinsame Anspruch der studierenden-zentrierten Lehre als wiederkehrendes Muster. Die mehrstufige Analyse legt offen, wie Lehrpersonen mit den Themen Beziehungsaufbau, Schaffung eines (digitalen) Raums sowie Sicherheit für Studierende umgehen und sich daraus Handlungsmuster entwickeln.

Language in the Age of Mechanical Reproduction - Thomas, Sven (Technology and Language)

Luna, Laureano. “Strengthening the Russellian Argument Against Abolutely Unrestricted Quantification”. Synthese 200 (2022), No. 3, Paper No. 182, 13 pp - Peckhaus, Volker (Mathematical Reviews)

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Piloteinsatz einer E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

Informal Workplace Learning at a Glance: Validation of Short Measure for White-Collar Workers. - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (European Association of Work and Organizational Psychology Congress 2022.)

Off Your Own Bat or Aided by Others: A Vignette Study on the Role of Metacognitions and Social Support for Informal Workplace Learning. - Decius, Julian; Knappstein, Michael; Seifert, Andreas (Hawaii International Conference On Education.)

Off Your Own Bat or Aided by Others? An Investment-Reward Typology of Metacognition and Social Support at Work. - Seifert, Andreas; Decius, Julian; Knappstein, Michael (EARLI SIG14 Conference)

Effects of Digital Transformation on Job Satisfaction and Employee Retention: An Integrative Framework - Depenbusch, Sarah; Schürmann, Mirko; Schaper, Niclas; Seifert, Andreas; Schumacher, Jan-Philip; Straatmann, Tammo

Digitaler Wechselunterricht in der gymnasialen Oberstufe – ein Modell mit Zukunft? - Rogge, Tim; Seifert, Andreas (AEPF-Tagung „Lehren und Lernen neu gedacht – Konsequenzen für das zukünftige Bildungswesen“)

Pädagogische Kompetenz als Ausgangspunkt beruflichen Könnens!? Ergebnisse der Kompetenzmessung angehender Lehrkräfte unter Berücksichtigung individueller Voraussetzungen. - Caruso, Carina; Seifert, Andreas (Religionspädagogische Beiträge. Journal for Religion in Education.)